2021
DOI: 10.3390/ijerph18199943
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy Levels among Italian Students: Monitoring and Promotion at School

Abstract: Health literacy was identified as an important determinant of health, particularly for adolescents. However, more efforts are needed to monitor this construct and provide inputs for policy development. This study aims to: (a) Assess the validity and reliability of the Italian version of the Health Literacy for School-Aged Children (HLSAC-I); (b) Identify the health literacy levels among Italian students and compare them with other countries’ levels; and (c) Identify the associations between health literacy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 51 publications
7
18
1
Order By: Relevance
“…In some respects, our results contrast studies in comparable countries such as the recent Danish 21 and Italian 18 validations of the HLSAC. Including all ten items in one dimension, the Danish study found an excellent fit with factor loadings ranging between 0.52 and 0.75, and good internal consistency (Cronbach's alpha = 0.86), while the Italian study demonstrated an acceptable fit.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In some respects, our results contrast studies in comparable countries such as the recent Danish 21 and Italian 18 validations of the HLSAC. Including all ten items in one dimension, the Danish study found an excellent fit with factor loadings ranging between 0.52 and 0.75, and good internal consistency (Cronbach's alpha = 0.86), while the Italian study demonstrated an acceptable fit.…”
Section: Discussioncontrasting
confidence: 99%
“…The HLSAC has been used across Europe and validated in Slovakia and Belgium 17 , Italy 18 , Poland 19 , France 20 , Denmark 21 and Turkey 22 . No validated instrument for measuring HL among Norwegian children and adolescents has been identified.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of a regional representative sample attests to the validity of the study, and the Lombardy region is a very populated area with a number of inhabitants compared to many European countries. Lastly, although subdimensions of health literacy could constitute better predictive factors leading to healthy behaviours, the Health Literacy for School-Aged Children (HLSAC) scale used in this study has a solid background [ 60 , 61 , 62 , 63 , 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Health Literacy for School-Aged Children (HLSAC) scale was used to measure self-reported health literacy [ 60 , 61 , 62 ]. The Italian version was validated by Velasco and colleagues [ 63 ]. The instrument includes 10 items (e.g., “Having good information regarding health”) on a 4-point Likert scale (1 = “Not at all true”; 4 = “Absolutely true”).…”
Section: Methodsmentioning
confidence: 99%
“…In order to optimize the role of medication literacy and patient empowerment in health management, those two components should be aligned to individual's cognitive, affective and behavioral abilities (Velasco et al, 2021). Childhood is a critical stage for development of fundamental cognitive, physical, and emotional processes.…”
Section: Introductionmentioning
confidence: 99%